Fruit and vegetable intakes and asthma in the E3N study. Issue 3 (5th January 2006) - Romieu, I; Varraso, R; Avenel, V; Leynaert, B; Kauffmann, F; Clavel-Chapelon, F
Abstract : Background: A study was undertaken to investigate whether dietary intake predicted the prevalence of adult asthma among French women participating in the E3N study. Methods: Of 68 535 women who completed a food frequency questionnaire in 1993 which included 238 food items, 2145 (3.1%) reported having asthma. The distribution of food intake was divided into quartiles (Q1 –Q4 ) and the prevalence of asthma was compared between the different quartiles (lowest as reference) using logistic regression models on cross sectional data. Results: After adjusting for age, body mass index, menopausal status, smoking status, total caloric intake, physical activity, and use of dietary supplements, women who had a greater intake of tomatoes (ORQ1–Q4 0.85 95% CI 0.75 to 0.96, test for trend p = 0.02), carrots (ORQ1–Q4 0.81 95% CI 0.72 to 0.92, test for trend p = 0.0003), and leafy vegetables (ORQ1–Q4 0.82 95% CI 0.73 to 0.93, test for trend p = 0.0009) had a lower prevalence of asthma. Apples were marginally related to the prevalence of asthma. No other fruits or vegetables were significantly associated with asthma prevalence. Conclusions: These results suggest that the intake of some vegetables may decrease the prevalence of adult asthma.